Root respiration in whole Haberlea rhodopensis Friv. plants during desiccation and rehydration - Péli, Evelin Ramóna (Acta Biologica Szegediensis, 2008)
The current study investigated changes in root respiration connection with root relative water content in whole Haberlea rhodopensis Friv. plant during desiccation and recovery phases. Whole plant was examined during full hydrated, 72 h dehydration and 96 h rehydration period every 6 and 24 hours continuously. Root respiration rates decreased during water stress while it has exceeded the starting values after rehydration. There was a linear relationship between relative water content and root respiration. H. rhodopensis whole plants were able to maintain root respiration for the whole desiccation period. The root respiration rate was linearly related to root tissue relative water content.